First survey of shallow-water Amphipoda along the Georgian Black Sea coast reveals new faunistic records and the unexpected Atlantic invader Melita nitida - COPILAȘ-CIOCIANU, DENIS; BERCHI, GAVRIL MARIUS; MUMLADZE, LEVAN (Mediterranean Marine Science, 2020)
We present findings from the first survey of shallow-water amphipods conducted along the Black Sea coast in Georgia. Eight species from five families have been identified, all but one being new for the Georgian fauna. Although most are usual inhabitants of the Black and Mediterranean seas, we report the first record of the invader Melita nitida in this region. This North American species was previously known in Europe only from the Atlantic and Baltic coasts. Its finding in the Black Sea implies either jump dispersal, or a more widespread, but cryptic distribution. Given that the total number of species reported in Georgia is lower than in the other countries neighbouring the Black Sea, we anticipate the discovery of new taxa in future surveys. Our study highlights the importance of faunistic exploration in previously overlooked regions for detecting potentially cryptic invasions and corroborating biogeographical patterns.